Presidents and Place: America's Favorite Sons - Cobb, Thomas; Akroyd, Olga Maria May (Lexington Books, 2023)
Presidents and Place: America's Favorite Sons highlights the interrelationship between America's leading political icons and various facets of space and place, including places of birth and death as well as regional allegiances, among others. The chapters examine the legacy of relationships between presidents and place in a variety of social and cultural forms, ranging from famous political campaigns to television series to developments in tourism. Beginning with the political iconography of New York's Federal Hall in early eighteenth-century America and ending with a focus on the Republican Party's electoral relationship with the South, the interdisciplinary and methodologically diverse nature of the chapters reveals that place has more than a biographical significance in relation to US presidents.